2015
DOI: 10.1016/j.semcdb.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Emerging trends in the pathophysiology of lymphatic contractile function

Abstract: Lymphatic contractile dysfunction is central to a number of pathologies that affect millions of people worldwide. Due to its critical role in the process of inflammation, a dysfunctional lymphatic system also compromises the immune response, further exacerbating a number of inflammation related diseases. Despite the critical physiological functions accomplished by the transport of lymph, a complete understanding of the contractile machinery of the lymphatic system lags far behind that of the blood vasculature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 132 publications
0
62
0
2
Order By: Relevance
“…Like vascular smooth muscle, lymphatic muscle contraction is regulated primarily by the balance of myosin light chain kinase (MLCK)/myosin light chain phosphatase (MLCP) activity controlling myosin light chain phosphorylation (reviewed in Chakraborty et al . a ). Lymphatic vessels resemble arterioles in that they develop basal tone and exhibit myogenic constriction to pressure elevation (Davis et al .…”
Section: Normal Lymphatic Pumpingmentioning
confidence: 99%
See 1 more Smart Citation
“…Like vascular smooth muscle, lymphatic muscle contraction is regulated primarily by the balance of myosin light chain kinase (MLCK)/myosin light chain phosphatase (MLCP) activity controlling myosin light chain phosphorylation (reviewed in Chakraborty et al . a ). Lymphatic vessels resemble arterioles in that they develop basal tone and exhibit myogenic constriction to pressure elevation (Davis et al .…”
Section: Normal Lymphatic Pumpingmentioning
confidence: 99%
“…The outer edges of the fluorescent border demarcate the inner diameter of the vessel, which becomes clear when the fluorescence ( Lymphatic muscle is non-striated and usually classified as vascular smooth muscle, but it shares biochemical and functional characteristics with both vascular and cardiac muscle (von der Weid & Zawieja, 2004). Like vascular smooth muscle, lymphatic muscle contraction is regulated primarily by the balance of myosin light chain kinase (MLCK)/myosin light chain phosphatase (MLCP) activity controlling myosin light chain phosphorylation (reviewed in Chakraborty et al 2015a). Lymphatic vessels resemble arterioles in that they develop basal tone and exhibit myogenic constriction to pressure elevation (Davis et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Lymphatic collecting vessels exhibit both sensitive regulation of vessel tone and also rhythmic large contractions that can be described in similar terms as the cardiac cycle . Physical stimuli such as shear stress (flow) and stretch (pressure), both have significant roles in the regulation of lymphatic contractions . In humans, the intrinsic contractions are responsible for transporting up to two‐third of lymph from the lower extremities, and failure of the lymphatic system results in a chronic and progressive disease called lymphedema …”
Section: Introductionmentioning
confidence: 99%
“…2 Physical stimuli such as shear stress (flow) and stretch (pressure), both have significant roles in the regulation of lymphatic contractions. 3 In humans, the intrinsic contractions are responsible for transporting up to two-third of lymph from the lower extremities, 4 and failure of the lymphatic system results in a chronic and progressive disease called lymphedema. 5 While genetic malformations are linked with primary lymphedema, the majority of lymphedema cases are secondary to other complications.…”
Section: Introductionmentioning
confidence: 99%
“…The lymphatic system, with its intrinsic physiologic functions in cellular homeostasis, immune cell trafficking, and lipid absorption (1113), contributes significantly to the pathogenesis of metabolic disorders (1417). We have demonstrated that lymphatic vessels from MetSyn rats exhibit impaired intrinsic contractile activity (18, 19).…”
mentioning
confidence: 99%